A thermodynamic adsorption/entrapment model for selenium(IV) coprecipitation with calcite - Heberling, F.; Vinograd, V.; Polly, R.; Gale, Julian; Heck, S.; Rothe, J.; Bosbach, D.; Geckeis, H.; Winkler, B. (Pergamon, 2014)
Selenium is an environmentally relevant trace element, while the radioisotope 79Se is of particular concern in the context of nuclear waste disposal safety. Oxidized selenium species are relatively soluble and show only weak adsorption at common mineral surfaces. However, a possible sorption mechanism for selenium in the geosphere is the structural incorporation of selenium(IV) (selenite, SeO3 2) into calcite (CaCO3). In this study we investigate the interactions between selenite and calcite by a series of experimental and computational methods with the aim to quantify selenite incorporation into calcite at standard conditions. We further seek to describe the thermodynamics of selenite-doped calcite, and selenite coprecipitation with calcite. The structure of the incorporated species is investigated using Se K-edge EXAFS (isotropic and polarization dependent) and results are compared to density functional theory (DFT) calculations. These investigations confirm structural incorporation of selenite into calcite by the substitution of carbonate for selenite, leading to the formation of a Ca(SeO3)X(CO3)(1-X)solid solution.Coprecipitation experiments at low supersaturation indicate a linear increase of the selenite to carbonate ratio in the solid with the increase of the selenite to carbonate ratio in the contact solution. This relationship can be described under the assumption of an ideal mixing between calcite and a virtual CaSeO3 endmember, whose standard Gibbs free energy (G0(CaSeO3_exp) = 953 ± 6 kJ/mol, log10(KSP(CaSeO3_exp)) = 6.7 ± 1.0) is defined by linear extrapolation of the excess free energy from the dilute Henry’s law domain to X(CaSeO3) = 1. In contrast to this experimental result, DFT and force field calculations predict the virtual bulk CaSeO3 endmember to be significantly less stable and more soluble: G0(CaSeO3 bulk) = 912 ± 10 kJ/mol and log10(KSP(CaSeO3_bulk)) = 0.5 ± 1.7. To explain this discrepancy we introduce a thermodynamic adsorption/entrapment concept. This concept is based on the idea that the experimental value of 953 ± 6 kJ/mol reflects the Gibbs free energy of CaSeO3 within the surface layer, while the value obtained from atomistic calculations reflects bulk thermodynamic properties. In coprecipitation experiments performed at steady-state conditions the difference between these values is compensated by the supersaturation. Thus, if the Gibbs free energies of the bulk CaCO3 and CaSeO3 endmembers are substituted with the Gibbs free energies of the surface endmembers, the coprecipitation experiment can still be treated within the formalism of equilibrium thermodynamics. This concept leads to a number of important consequences, which can be tested both experimentally and theoretically.We show that selenite adsorption at the calcite surface and selenite coprecipitation with calcite under supersaturated conditions can be described with the same partition coefficient. This implies that the coprecipitation can be viewed as a sequence of adsorption and entrapment events. On the other hand, our aragonite recrystallization experiments show that at near equilibrium conditions the calcite growth is inhibited in the presence of selenite. Consistent with these observations, our DFT calculations show that the substitution of carbonate for selenite is energetically more favorable at the surface than inside the bulk. The whole set of the experimental and atomistic simulation results leads to the conclusion that the calcite–CaSeO3 solid solution can only grow continuously if the aqueous solution is supersaturated with respect to the bulk solid solution. Under these conditions selenite coprecipitates with calcite at a partition coefficient of D = 0.02 ± 0.01. If the solution is undersaturated with respect to the bulk solid solution, only surface ion-exchange occurs. Elevated selenite concentrations in bulk calcite therefore reflect non-equilibrium conditions.